Fusion of ICT and Differentiated Instruction in Developing Lesson Plan: Boosting EFL Learners Hortatory Text Mastery - Fahmi Al Fiqri; Yuliati; Sri Wahyuni (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2025)
Students and teachers' need for familiarity with the fusion of technology-based and differentiated lesson planning contributes to challenges for recent education. The goal of the project is to make language learning more successful by meeting the demands of teachers in terms of lesson plan development, implementing differentiated instruction, and using information and communication technology. This research employs five steps of research and development methods: 1) the preliminary research stage, 2) the development stage, 3) the expert validation stage, 4) the testing stage, and 5) the dissemination stage. The study involved 22 senior high school students, an English teacher, and a lesson plan validator expert. The results from the development of Information and Communication Technology (ICT) combined with Differentiated Instruction (DI) in a lesson plan for teaching hortatory exposition text to eleventh-grade senior high school students are considered ready to implement and disseminate with a score of 100 from the teacher as a validator. This lesson plan significantly improved students' learning motivation and ability in hortatory exposition text based on the data analysis. The findings suggest that integrating ICT and DI in lesson planning enhances students' engagement and performance and provides an adaptable model for teachers to implement technology-supported differentiated instruction.